SKILLS-BASED ECLECTIC TECHNIQUES MATRIX FOR ELT MICROTEACHINGS - İskender Hakkı Sarıgöz (Informascope, 2016)
Abstract Foreign language teaching undergoes constant changes due to the methodological improvement. This progress may be examined in two parts. They are the methods era and the post-methods era. It is not pragmatic today to propose a particular language teaching method and its techniques for all purposes. The holistic inflexibility of mid-century methods has long gone. In the present day, constructivist foreign language teaching trends attempt to see the learner as a whole person and an individual who may be different from the other students in many respects. At the same time, the individual differences should not keep the learners away from group harmony. For this reason, current teacher training programs require eclectic teaching matrixes for unit design considering the mixed ability student groups. These matrixes can be prepared in a multidimensional fashion because there are many functional techniques in different methods and other new techniques to be created by instructors freely in accordance with the teaching aims. The hypothesis in this argument is that the collection of foreign language teaching techniques compiled in ELT microteachings for a particular group of learners has to be arranged eclectically in order to update the teaching process. Nevertheless, designing a teaching format of this sort is a demanding and highly criticized task. This study briefly argues eclecticism in language-skills based methodological struggle from the perspective of ELT teacher education. Key words: FLT, ELT, teacher training, ELT microteachings, eclectic matrix